2000
DOI: 10.1046/j.1444-2906.2000.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

cDNA cloning of myosin rod and the complete primary structure of myosin heavy chain of walleye pollack fast skeletal muscle

Abstract: SUMMARY: The amino acid sequences of myosin rod containing subfragment‐2 (S2) and light meromyosin (LMM) were determined by cDNA cloning for walleye pollack fast skeletal myosin heavy chain. While S2 and LMM were composed of 442 and 656 amino acid residues, a total of 1937 amino acid residues accounted for the whole myosin heavy chain molecule with previously determined sequence for the subfragment‐1 heavy chain region of this fish. Both regions for S2 and LMM showed a seven‐residue repeat pattern characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 26 publications
2
35
0
Order By: Relevance
“…The comparison of deduced amino acid sequences of brushtooth and wanieso lizardfish MYH with those of other sequences is presented in Table 4. The highest sequence identity of bMYH3 was 97% to wMYH1, followed by MYH from white croaker 6 (AB039672), walleye pollack 11,12 (AB017819 and AB000214), carp acclimated to 10°C 21,22 (D89990) and rabbit (U32574) in the decreasing order. Brushtooth and wanieso lizardfish MYH showed the amino acid sequence identity of 92–93% to white croaker MYH, which was higher than that of 90% to walleye pollack MYH.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The comparison of deduced amino acid sequences of brushtooth and wanieso lizardfish MYH with those of other sequences is presented in Table 4. The highest sequence identity of bMYH3 was 97% to wMYH1, followed by MYH from white croaker 6 (AB039672), walleye pollack 11,12 (AB017819 and AB000214), carp acclimated to 10°C 21,22 (D89990) and rabbit (U32574) in the decreasing order. Brushtooth and wanieso lizardfish MYH showed the amino acid sequence identity of 92–93% to white croaker MYH, which was higher than that of 90% to walleye pollack MYH.…”
Section: Resultsmentioning
confidence: 99%
“…Despite very high amino acid sequence identity between MYH of the above two fish species, 10–13 the corresponding myosins showed striking differences in polymer‐forming ability, viscoelasticity and thermodynamic properties possibly caused by species‐specific substitutions of some particular amino acids 7–9 . Three myosin fragments of white croaker, S1, S2 and LMM, exhibited 79–94% sequence identities to the corresponding fragments of various vertebrates, including walleye pollack.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…3), confirmed that common carp embryonic MYH emb1 and MYH emb2 both belong to a fast type, whereas MYH emb3 does to a slow/cardiac type. MYH emb1 and MYH emb2 formed a monophyletic clade with zebrafish myhz2 and myhc4 (Xu et al, 2000;Peng et al, 2002;Nihei et al, 2006), and these MYHs formed one group with brushtooth lizardfish MYH Su Fast (Hossain et al, 2008), wanieso lizardfish MYH Sw Fast (Hossain et al, 2008), chum salmon MYH Ok Fast (Ojima et al, 1998), walleye pollack MYH Tc Fast (Togashi et al, 2000), yellowbelly rockcod MYH Nc fast (Gauvry et al, 2000), torafugu MYH M743-2 (Ikeda et al, 2004;Ikeda et al, 2007) and white croaker MYH Pa Fast (Yoon et al, 2000) (see Fig. 3).…”
Section: Mandibular Archmentioning
confidence: 99%